2014
DOI: 10.1098/rsfs.2013.0051
|View full text |Cite
|
Sign up to set email alerts
|

On growth and form ofBacillus subtilisbiofilms

Abstract: A general feature of mature biofilms is their highly heterogeneous architecture that partitions the microbial city into sectors with specific micro-environments. To understand how this heterogeneity arises, we have investigated the formation of a microbial community of the model organism Bacillus subtilis . We first show that the growth of macroscopic colonies is inhibited by the accumulation of ammoniacal by-products. By constraining biofilms to grow approximately as two-dimensional la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 66 publications
4
66
0
Order By: Relevance
“…The model builds on that developed in (23) and considers the interaction of the following basic processes (see Fig 4).…”
Section: Mathematical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The model builds on that developed in (23) and considers the interaction of the following basic processes (see Fig 4).…”
Section: Mathematical Frameworkmentioning
confidence: 99%
“…Over time, the initial founding cell population divides and expands across the surface in an extracellular matrix dependent manner (18,23,24). However, after a period of 2-3 days, expansion of the biofilm stops.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on B. subtilis biolm formation on solid substrates as in the case of this study, many of these mathematical and experimental investigations 27,28,32,33 analyzed how nutrient availability affects biolm growth 27,28,32 or how bacterial division generates pressure that leads to the spreading of biomass in B. subtilis biolms. 33 Other mathematical models describe B. subtilis biolm formation at the air-liquid interface. subtilis biolm formation at the air-liquid interface that accounts for two different bacterial phenotypes: motile cells and matrix-producing cells.…”
Section: 54mentioning
confidence: 99%
“…28,31,32 For example, it has been suggested that the physical mechanism responsible for the spreading of biomass in B. subtilis biolms is the pressure generated by bacterial division. 33 Two growth parameters that are typically used to describe the dimensions of a biolm are the area covered by the biolm and the biolm height. 34 However, it remains unclear how the different molecular components of the biolm matrix quantitatively modulate B. subtilis biolm growth.…”
Section: Introductionmentioning
confidence: 99%
“…Here we can show that typical mobility laws give stable fronts or weekly unstable fronts. The main conclusion however is that if we want to interpret epithelia or a priori biofilms [37], elastic effects must be introduced which is possible in the mixture model framework [23] as it has been done for tumor growth. Ultimately, the comprehension of the shape instability and the pattern formation in multiphase models is of utmost importance for a wide range of problems relating to tissue growth, remodeling and morphogenesis under chemotaxis.…”
Section: Resultsmentioning
confidence: 99%